Special Issue: Hot Topics in Internal Medicine - Miftahussurur, Muhammad (Gaceta Médica de Caracas, 2023)
For the past years, COVID-19 has drawn attention and has become a global burden. It affected almost all countries around the world and has had a catastrophic effect resulting in over 278 million cases and 5.4 million deaths worldwide. Not only does it cause pulmonary complications, but it also affects other organ systems. Within this special issue, a systematic review by Gianto et al. highlighted the need to consider acute kidney injury when managing COVID-19 patients as it contributed and/or correlated with disease severity, prognosis, and mortality. In addition, COVID-19 can also aggravate the severity of concomitant diseases, as presented by Kandinata et al. showing that hypoglycemia in a patient suffering from insulinoma and hydrocephalus was amplified by COVID-19.